THE FIRST FERMI LARGE AREA TELESCOPE CATALOG OF GAMMA-RAY PULSARS - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; et al. (Astrophysical Journal Supplement Series, 2010)
The dramatic increase in the number of known gamma-ray pulsars since the launch of the Fermi Gamma-ray Space Telescope (formerly GLAST) offers the first opportunity to study a sizable population of these high-energy objects. This catalog summarizes 46 high-confidence pulsed detections using the first six months of data taken by the Large Area Telescope (LAT), Fermi's main instrument. Sixteen previously unknown pulsars were discovered by searching for pulsed signals at the positions of bright gamma-ray sources seen with the LAT, or at the positions of objects suspected to be neutron stars based on observations at other wavelengths. The dimmest observed flux among these gamma-ray-selected pulsars is 6.0 x 10(-8) ph cm(-2) s(-1) (for E > 100 MeV). Pulsed gamma-ray emission was discovered from 24 known pulsars by using ephemerides (timing solutions) derived from monitoring radio pulsars. Eight of these new gamma-ray pulsars are millisecond pulsars. The dimmest observed flux among the radio-selected pulsars is 1.4 x 10(-8) ph cm(-2) s(-1) (for E > 100 MeV). The remaining six gamma-ray pulsars were known since the Compton Gamma Ray Observatory mission, or before. The limiting flux for pulse detection is non-uniform over the sky owing to different background levels, especially near the Galactic plane. The pulsed energy spectra can be described by a power law with an exponential cutoff, with cutoff energies in the range similar to 1-5 GeV. The rotational energy-loss rate ((E) over dot) of these neutron stars spans five decades, from similar to 3 x 10(33) erg s(-1) to 5 x 10(38) erg s(-1), and the apparent efficiencies for conversion to gammaray emission range from similar to 0.1% to similar to unity, although distance uncertainties complicate efficiency estimates. The pulse shapes show substantial diversity, but roughly 75% of the gamma-ray pulse profiles have two peaks, separated by greater than or similar to 0.2 of rotational phase. For most of the pulsars, gamma-ray emission appears to come mainly from the outer magnetosphere, while polar-cap emission remains plausible for a remaining few. Spatial associations imply that many of these pulsars power pulsar wind nebulae. Finally, these discoveries suggest that gamma-ray-selected young pulsars are born at a rate comparable to that of their radio-selected cousins and that the birthrate of all young gamma-ray-detected pulsars is a substantial fraction of the expected Galactic supernova rate.
CRIS-Team WoS Importer:2020-01-15